Figury kinetyczne w literaturze cyfrowej. Stan badań i kilka wątpliwości - Winiecka, Elżbieta (Załącznik Kulturoznawczy, 2021)
The article presents the state of research on kinetic e-literature. New digital phenomena – combining the issues of visual arts, technology and literature – encourage the redefinition of the latter category in literary studies. Literature in the digital space ceases to be only the art of the word. It uses techniques and codes of other arts, including movement as a new feature, inaccessible to printed literature. In her analysis, the author focuses on this last feature of electronic content. The article recapitulates the state of research on poetics and rhetoric of animated texts. It also discusses methodological problems related to the study of digital literature and presents some examples of rhetorical kinetic figures. The author notes that interpretations of new phenomena in the literary field, grounded in the rhetorical tradition supported by twentieth-century semiotic research, are insufficient to explain all the problems related to digital technology in the humanities. In the conclusion, she points to the need for further research on changes in readers’ perception and literary communication.